General Approach to Regions of Variability via Subordination of Harmonic Mappings - Sh. Chen; S. Ponnusamy; X. Wang (International Journal of Mathematics and Mathematical Sciences)
Using subordination, we determine the regions of variability of several subclasses of harmonic mappings. We also graphically illustrate the regions of variability for several sets of parameters for certain special cases.